Crisis Response, Reputation, and Loyalty in the Pertamina Scandal - Abhirama Swastyayana Dian Perdana; Mohammad Shihab (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2026)
This study examines how crisis response strategy influences brand reputation, consumer sentiment, and customer loyalty during Pertamina’s 2025 corporate scandal in Indonesia, with social media engagement tested as a moderating factor. Adopting a quantitative design, the study employed Partial Least Squares Structural Equation Modeling to analyze survey data from 112 respondents exposed to the crisis. The results show that accommodative strategies significantly enhance brand reputation and generate more positive consumer sentiment, both of which strongly predict customer loyalty. Although the moderating role of social media engagement was not statistically significant, conditional analysis suggests its influence on how stakeholders interpret and react to crisis messages. The study confirms that emotional and cognitive evaluations jointly shape loyalty outcomes in ethically charged crises. These findings highlight the importance of culturally sensitive crisis communication strategies and underscore the need to integrate digital engagement dynamics in public relations responses within collectivist and highly networked societies.